Assessing the Effectiveness of Problem-Based Learning on the Academic Performance of Grade XII Students - Yuniati, Erni (Nexus Publishing NXP, 2024)
Traditional teaching methods often fall short in cultivating critical thinking skills, real-world application, and student engagement, which are crucial for academic success and future readiness. These shortcomings can result in passive learning, limited problem-solving abilities, and a disconnect between theoretical knowledge and practical application, ultimately hindering students’ overall academic performance. To address these issues, this study aimed to examine the effectiveness of problem-based learning (PBL) as an alternative teaching method for enhancing the academic performance of Grade XII students at MAN 1 Kota Madiun. Utilizing a pre-experimental design, the research focused on a single class, specifically Class XII-IPS 2, with a sample of 32 students during the second semester of the 2021/2022 academic year. The topic investigated was “How to Prepare Your Future”. The study evaluated the impact of implementing PBL on the students’ academic performance by examining their engagement, critical thinking skills, and ability to apply their knowledge to real-life situations. The findings revealed that PBL significantly enhanced the students’ academic performance, leading to higher engagement, improved critical thinking, and better application of knowledge in real-world contexts. Students showed increased participation and initiative, developed sharper analytical and evaluative skills, and effectively transferred classroom learning to practical situations. These outcomes highlight PBL’s effectiveness in not only boosting academic achievement but also equipping students with vital skills for future success. The study suggests that educators and policymakers should integrate PBL into curricula to foster critical thinking and real-world problem-solving abilities, thereby better preparing students for academic and life challenges.